The use of stem cells in the treatment of diabetes mellitus and its complications - review - Ochyra, Łukasz; Łopuszyńska, Anna (Journal of Education, Health and Sport, 2024)
Introduction and purpose Diabetes is a disease resulting from impaired action or secretion of insulin. The number of patients currently amounts to approximately 422 million, and approximately 1.5 million deaths per year are directly attributed to this disease. Diabetes significantly reduces the quality of life and, if poorly controlled, can lead to serious complications. Mesenchymal stem cells are multipotent cells capable of differentiation. They have the ability to self-renew and have a modulating function. There are reports that they can be used in the treatment of this disease. The aim of the review was to present a new method of therapy and their possible effects. Material and methods The review was based on articles obtained from PubMed scientific database in the years 2015-2023, using the following keywords: diabetes mellitus, stem cells, diabetes complications. Results Implanted stem cells are able to transform into cells that produce and secrete insulin, and also enable better glycemic control. They can alleviate chronic inflammation and reduce fibrosis. Taking into account the complications that occur during long-term diabetes, the use of stem cells may be associated with improving the function of specific organs and tissues such as the kidneys, heart, eyes and nerves. Studies also report a positive effect of these cells on the healing process of wounds and ulcers. Conclusions Stem cells are a promising object of analysis. They can control glycemia and have a positive effect on the functioning of the kidneys, heart, eyes and nerves, and accelerate wound healing, but further, extensive research is needed to assess the effectiveness and safety of this therapy.